Goal orientations, motivational climate, and prosocial and antisocial behaviour in youth football: Exploring their temporal stability and reciprocal relationships - Sage, L. D.; Kavussanu, M. (Journal of Sports Sciences, 2008)
In this study, we examined the temporal stability and reciprocal relationships among task and ego orientation, task- and ego-involving climates, and prosocial and antisocial behaviour in youth football. Male (n = 156) and female (n = 24) footballers (mean age 14.1 years, s = 1.8) completed questionnaires towards the beginning and end of a regular season. Questionnaires measured goal orientation, perceived motivational climate, and frequency of prosocial and antisocial behaviours. Structural equation modelling indicated moderate covariance stability between the beginning and end of the season. Subsequent analyses revealed a significant decrease only in perceptions of task-involving climate. In the cross-lagged analyses, prosocial behaviour at the beginning of the season positively predicted task-involving climate at the end of the season. Antisocial behaviour at the beginning of the season positively predicted both ego orientation and ego-involving climate at the end of the season and a reciprocal relationship was revealed whereby ego orientation at the beginning of the season positively predicted antisocial behaviour at the end of the season. Task orientation at the beginning of the season negatively predicted ego-involving climate at the end of the season. All cross-lagged relationships were weak. This exploratory study offers limited support for bi-directional relationships between personal, environmental, and behavioural variables but provides useful insight into the covariance stability, change, and interrelationships between motivational and moral constructs over a competitive season.